Optic nerve head blood flow regulation during changes in arterial blood pressure in patients with primary open-angle glaucoma - Bata, Ahmed M. (2020)
Purpose: Abnormal autoregulation of optic nerve head blood flow (ONHBF) has been postulated to play an important role in primary open‐angle glaucoma (POAG). We used laser Doppler flowmetry (LDF) to estimate quantitatively the ONHBF and compared ONHBF autoregulation between glaucoma patients and healthy controls during isometric exercise. Methods: Forty patients with POAG and 40 healthy age‐ and sex‐matched subjects underwent three periods of isometric exercise, each consisting of 2 min of handgripping. Optic nerve head blood flow (ONHBF) was measured continuously using LDF. Systemic blood pressure, intraocular pressure and ocular perfusion pressure were assessed in all participants. Results: Isometric exercise was associated with an increase in ocular perfusion pressure during all handgripping periods in both groups (p < 0.001). However, there was no change in ONHBF in either group. Three of the glaucoma patients and two of the healthy subjects showed a consistent 10% decrease in blood flow during isometric exercise, in spite of an increase in their blood pressure. This difference between groups was not significant (p = 0.61). Four other glaucoma subjects showed a consistent increase in blood flow of more than 10% during isometric exercise, whereas this was not seen in healthy subjects (p = 0.035). Conclusion: This study suggests that abnormal ONHBF autoregulation is more often seen in patients with POAG than healthy control subjects. The relationship to the glaucoma disease process is currently unknown and requires further investigation.